Pear Performance as Affected by the Application of Some Nano Fertilizers in Combination with Biochar as a Biostimulant Under Drought Conditions - Khalid F. Almutairi; Krzysztof Górnik; Ragheb M. El Adly; Walid F. A. Mosa (BioResources, 2024)
Drought is an environmental stress that can negatively influence growth and productivity of fruit trees because it decreases the photosynthetic rate and stomatal conductance and raises the rate of water loss from the plant surfaces. Therefore, this study investigated the soil application of biochar individually or in combination with the spraying of boron, silicon, and molybdenum relative to the growth attributes, fruit drop percentages, yield, and fruit quality of Le Conte pear trees grown under drought stress. The trees were fertilized by biochar at 0, 1, and 2 kg per tree individually or in combination with the foliar spraying with 0 mg B2O3 + 0 mg SiO2 + 0 mg MoO2, 10 mg B2O3 + 25 mg SiO2 + 25 mg MoO2, 20 mg B2O3 + 50 mg SiO2 + 50 mg MoO2 and 30 mg B2O3 + 75 mg SiO2 + 75 mg MoO2 at start of February, start of March and start of April, compared to untreated trees (control). The results showed that the soil addition of biochar or spraying of nano fertilizers individually or in combinations improved the vegetive growth, productivity and fruit quality, and leaf mineral content, meanwhile they reduced the fruit drop. The best results were obtained by the application of 2 kg biochar combined with 30 mg B2O3 + 75 mg SiO2 + 75 mg MoO2, which was superior to other applied treatments in the two seasons.